Analytical and numerical modeling of shallow water flow in a channel: theoretical approaches and simulations - Bacharou, Taofic; Sabi Takou, Daniel; Adetola, Jamal (Zielona Góra: Uniwersytet Zielonogórski)
This study focuses on the modeling and simulation of shallow water flows in a channel through the application of the Saint-Venant equations. Two main approaches were explored: an analytical solution and a numerical method based on finite difference discretization. The analytical solution provides exact expressions for water depth and velocity under simplified conditions serving as a benchmark for validating numerical simulations.
Keywords: flow modeling; water depth; rectangular channel; Froude number; numerical simulation